Innowacyjność małych i średnich przedsiębiorstw w procesie globalizacji i integracji europejskiej - Jastrzębska, Władysława; Bobrecka-Jamro, Dorota; Tobiasz-Salach, Renata (MITEL, 2006)
Z artykułu wynika, że ​​w środowisku globalizacji i integracji występuje wiele problemy, które muszą być rozwiązane, aby utrzymać pozycję konkurencyjną małych i średnich przedsiębiorstw. Unijna i lokalna polityka innowacyjna uznawana jest za ważny czynnik konkurencyjności i innowacyjności przedsiębiorstw. Autor na podstawie wyników badań przedstawia ich opinię na temat możliwości rozwoju innowacji.

The paper shows, that in the environment of globalization and integration occurs many problems which must be solved to held competitivness position of small and medium enterprises. The EU- and local innovation policy is recognized as an important factor of competition and innovation of enterprises. The author on the basis of results of research presents their opinion concerning the opportunities for the innovations development.
Innovation Activity of Small and Medium Sized Enterprises in the Process of Globalization and Integration